Vitamin D deficiency as a potential risk factor for thyroid cancer: a clinical perspective - Yang, Jing; Wu, Tianyu; Chang, Xiaoying; Pan, Yue; Gong, Jian; Yang, Chuanjia (Frontiers in Nutrition, 2025)
ObjectivesVitamin D deficiency has garnered increasing attention as a potential risk factor for thyroid dysfunction and oncological progression. This study was designed to investigate the relationship between preoperative vitamin D status and postoperative complications in patients undergoing thyroidectomy.MethodsThis prospective cohort study investigated the association between preoperative vitamin D status and postoperative outcomes in a cohort of 120 patients following thyroidectomy for benign or malignant thyroid disease at Shengjing Hospital, China (2020–2022). Participants were stratified into three groups based on serum 25-hydroxyvitamin D [25(OH)D] concentrations: deficient (<20 ng/mL), insufficient (20–30 ng/mL), and sufficient (>30 ng/mL).ResultsVitamin D-deficient patients exhibited higher preoperative TSH levels (4.8 ± 1.6 vs. 2.7 ± 0.9 mIU/L, p < 0.001), lower free T3/T4, and reduced serum calcium (8.5 ± 0.6 vs. 9.1 ± 0.5 mg/dL, p = 0.004) compared to sufficient patients. After operation, vitamin D deficiency was associated with increased odds of hypocalcemia (OR: 4.17, 95%CI: 1.31–13.35, p = 0.01) and hypothyroidism (OR = 2.91, 95%CI: 1.14–7.42, p = 0.02) after adjustment for potential confounders.ConclusionThe findings of this study indicate that preoperative screening for, and subsequent correction of, vitamin D deficiency could lead to improved postoperative recovery and a reduction in complications among patients undergoing thyroidectomy. Further research is needed to establish causal relationships and explore the underlying mechanisms linking vitamin D status to thyroid function and surgical outcomes.